Mechanistic insights into the regression of atherosclerotic plaques - Song, Jianshu; Cao, Ce; Wang, Ziyan; Li, Haoran; Yang, Lili; Kang, Jing; Meng, Hongxu; Li, Lei; Liu, Jianxun (Frontiers in Physiology, 2024)
Atherosclerosis is a major contributor to cardiovascular diseases and mortality globally. The progression of atherosclerotic disease results in the expansion of plaques and the development of necrotic cores. Subsequent plaque rupture can lead to thrombosis, occluding blood vessels, and end-organ ischemia with consequential ischemic injury. Atherosclerotic plaques are formed by the accumulation of lipid particles overloaded in the subendothelial layer of blood vessels. Abnormally elevated blood lipid levels and impaired endothelial function are the initial factors leading to atherosclerosis. The atherosclerosis research has never been interrupted, and the previous view was that the pathogenesis of atherosclerosis is an irreversible and chronic process. However, recent studies have found that the progression of atherosclerosis can be halted when patients’ blood lipid levels are reversed to normal or lower. A large number of studies indicates that it can inhibit the progression of atherosclerosis lesions and promote the regression of atherosclerotic plaques and necrotic cores by lowering blood lipid levels, improving the repair ability of vascular endothelial cells, promoting the reverse cholesterol transport in plaque foam cells and enhancing the ability of macrophages to phagocytize and clear the necrotic core of plaque. This article reviews the progress of research on the mechanism of atherosclerotic plaque regression. Our goal is to provide guidance for developing better therapeutic approaches to atherosclerosis by reviewing and analyzing the latest scientific findings.